Surveys on electronic money - Yuksel Gormez; Forrest Capie (Bank of Finland, 2000)
This paper investigates the views of electronic money operators and innovators on the possibilities and implications of e-money, especially with respect to replacing central bank money as well as technical issues regarding e-money, its implications for the financial industry and central banking.This has been done using surveys of major e-money innovators and operators, based on the assumption that these operators and innovators are likely to shape the future framework for e-money schemes.It seems that innovators and operators are quite confident about the future of e-money - despite problems and obstacles surrounding current testing -and that central banks' monopoly of the issuance of money as a medium of exchange will no longer be unchallenged.
URN:NBN:fi:bof-20140807624
Keywords: 330